FROM DEVELOPMENTAL NEEDS TO PARENTAL ASPIRATIONS: TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS IN TASKA - NOR ZAWANI SABIL; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This library research explores the implementation of teaching and learning approaches for infants and toddlers in Malaysian childcare centres (TASKA) and examines how these practices meet the aspirations of today’s parents. The study focuses on identifying developmentally appropriate strategies that support the holistic growth of children under the age of four. Using a library-based method, various academic sources, journals, and policy documents were analysed to gain insights into effective teaching practices, theoretical foundations, and the expectations of modern parents. The findings reveal that TASKA aim to promote early stimulation, emotional security, and foundational learning through play-based and interactive approaches. However, several challenges persist, including limited resources, high teacher–child ratios, and a mismatch between parental expectations and pedagogical principles. To address these issues, this report suggests strengthening parental awareness, enhancing teacher training, improving facilities, and fostering stronger family–centre collaboration. The research concludes that balancing developmental appropriateness with parental aspirations is key to improving the quality of early childhood education in Malaysia.